RELATIONSHIP BETWEEN ORAL HEALTH SYMPTOMS AND MENTAL HEALTH AMONG ADOLESCENTS - Pipiet Okti Kusumastiwi; Rr. Tesaviani Kusumastiwi; Wustha Farani; Tri Wahyuni Sukesi (Cakradonya Dental Journal, 2026)
Adolescence is a critical developmental phase marked by increased vulnerability to mental health problems, which significantly impact various aspects of well-being, including oral health. The aim was to analyze the relationship between mental health and the experience of oral symptoms among adolescents in Kotagede, Yogyakarta, Indonesia. This cross-sectional analytical study involved 60 adolescents aged 10–19 years. Data were collected using structured questionnaires assessing general characteristics, mental health, and oral symptoms. Chi-square tests and logistic regression were used for analysis. The study found significant associations between mental health and oral symptoms. Higher levels of depression, anxiety (mild to severe), and stress (slight to high) were significantly related to increased incidences of toothache and gingival bleeding. Adolescents experiencing sadness, hopelessness, loneliness, and suicidal ideation were also more likely to report oral health problems. Gingival bleeding was particularly associated with psychological stressors. These findings suggest that physiological mechanisms and behavioral changes mediate the connection between mental and oral health.